2007
DOI: 10.1007/s11581-007-0122-y
|View full text |Cite
|
Sign up to set email alerts
|

Nano-ionic thin films of gadolinia-doped ceria prepared by pulsed laser ablation

Abstract: Microstructural properties of nano-ionic thin films of gadolinia-doped ceria (GDC) prepared by pulsed laser ablation from sintered targets of gadolinia (5-20 mol%) doped ceria are investigated. The ionic conductivity measurements of the sintered pellets showed a decrease in the activation energy from 1.1 to 0.65 eV for 5 and 30 mol% gadolinia-doped ceria, respectively. The microstructural properties of the GDC films as a function of substrate temperature, oxygen partial pressure, and laser energy show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…The spectra of the thin films have shown (1 1 1), (2 0 0), (2 2 0) and 3 1 1reflections. Due to increase in oxygen partial pressure the film orientation is found to alter from (1 1 1) to (2 0 0) plane in the partial pressure range 50-200 mTorr [24]. The intensity of the peak corresponding to (2 0 0) reflection is found to increase with an increase in oxygen partial pressure.…”
Section: X-ray Diffractionmentioning
confidence: 88%
See 1 more Smart Citation
“…The spectra of the thin films have shown (1 1 1), (2 0 0), (2 2 0) and 3 1 1reflections. Due to increase in oxygen partial pressure the film orientation is found to alter from (1 1 1) to (2 0 0) plane in the partial pressure range 50-200 mTorr [24]. The intensity of the peak corresponding to (2 0 0) reflection is found to increase with an increase in oxygen partial pressure.…”
Section: X-ray Diffractionmentioning
confidence: 88%
“…Many research articles in the literature are reported as the preparation of doped ceria thin films by chemical or physical methods such as spray pyrolysis [16], atomic layer deposition [17], sol-gel spin coating [18], dip-coating [19], metalorganic deposition [20], pulsed laser deposition [21]. Among these numerous deposition techniques, the pulsed laser deposition method is an unique and simple technique that can be used to prepare extremely good quality films from a wide variety of materials and compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced conductivity is attributed due to the formation of oxygen defect (V o ‫)״‬ in the ceria lattice by the introduction of aliovalent dopants [34]. Among the various trivalent dopants, Gd 3+ ion has found increased ionic conductivity at doping level of 5-30 mol% with ceria [35][36][37][38][39]. Therefore the combination of NiO-GDC composite would serve the purpose of fabrication of anode or anode precursor material for IT-SOFC.…”
Section: Where O Xmentioning
confidence: 99%
“…3 .6H 2 O) were mixed initially in a quartz beaker. Glycine nitrate was added to the mixed metal nitrate solution.…”
Section: Powder Synthesismentioning
confidence: 99%
“…In the last decade, nanocrystalline materials have been widely accepted to have a high potential to overcome these constraints. Nano-ionic ceramic oxides are displaying electrical properties which appear to be unique and may lead to applications that are not attainable by conventional microcrystalline oxides [3]. The ionic conductivity has been found significantly enhanced in nanocrystalline materials compared to the microcrystalline ones [4].…”
Section: Introductionmentioning
confidence: 99%